A neuro-fuzzy method on blending of materials - Çinar, Ahmet; Arslan, Ahmet (My University, 2003)
In this paper, a neuro-fuzzy technique for blending on the computer environment is proposed. In the classical blending process, while making the blending, the blend region has to know. In this study, blend surfaces are generated by means of neural networks and its control is achieved by fuzzy logic technique. Thus, the full-control blending surface is obtained. A feed forward, unsupervised artificial neural network is employed for computing blend surface. Firstly, the weights on the artificial neural networks is randomly selected and then weight adjustment on the networks is done by fuzzy logic technique. The proposed method is applied to distinct objects as application.
Nesne kaynaştirma işlemiçin sinirsel-bulanik tekni?i tabanli bir yöntem
Keywords: Blending; Feed forward unsupervised artificial neural network model; Fuzzy logic technique